Prevalence and Knowledge about Genital and other Warts among Students in Sulaimani Polytechnic University: A cross-sectional study - Karadaghy, Burhan; Mustafa Kamal, Niaz; Othman, Nasih (Kurdistan Journal of Applied Research, 2018)
Genital warts and other warts are an epidermal manifestation attributed to the epidermotropic human papillomavirus (HPV) some of which have been linked directly to an increased neoplastic risk in men and women. According to our knowledge, research is scarce and little is known about this condition in Sulaimani city. A cross-sectional study was carried out from 1st April to 30th May 2018 including 441 undergraduate students aged between 18-30 years belonging to the health and non-health colleges of Sulaimani Polytechnic University. Data were obtained on the knowledge about genital warts through self-administrated questionnaire from the students. Data were analyzed using STATA 11. The mean age of the participants was 21.3 years. Hand warts were the commonest types among participants (31%). Knowledge score ranged from 0 to 9, was not normally distributed with a median of zero (IQR 0-22), 89% of the students had very low knowledge score. Knowledge score correlated with socio-demographic parameters were significantly higher in health students (P <0.001); outside Sulaimani city (P= 0.01) and students aged 21-30 (P <0.001). In general, it is highlighting the need for communication and education among students in order to overcome the lack of knowledge about genital warts and HPV infection. It also might reflect higher health consciousness among Sulaimani university students.